2016
DOI: 10.18632/oncotarget.10040
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of MDA-9/Syntenin (SDCBP) expression in the microenvironment dampens tumor-supporting inflammation and inhibits melanoma metastasis

Abstract: Cancer development and progression to metastasis is a complex process, which largely depends on bidirectional communication between tumor cells and their microenvironment. Melanoma differentiation associated gene-9 (mda-9, also known as Syntenin-1, SDCBP), a gene first cloned by our group, is robustly expressed in multiple cancers including melanoma and contributes to invasion and metastasis in a tumor cell-intrinsic manner. However, the role of MDA-9/Syntenin in the tumor cell-extrinsic microenvironment remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 74 publications
3
29
1
Order By: Relevance
“…Despite the evidence for the above, but consistent with previous studies in mice by others 45 , 46 , syntenin-KO mice are viable, show no major defects and have normal fertility. This is surprising, given the broad expression of the syntenin protein in fetal and adult human 27 and mouse tissues 47 and the lethality of the corresponding morpholino-mediated knock downs in zebra fish and Xenopus , where syntenin is required for polarized early embryonic cell movements 48 , 49 .…”
Section: Discussionsupporting
confidence: 88%
“…Despite the evidence for the above, but consistent with previous studies in mice by others 45 , 46 , syntenin-KO mice are viable, show no major defects and have normal fertility. This is surprising, given the broad expression of the syntenin protein in fetal and adult human 27 and mouse tissues 47 and the lethality of the corresponding morpholino-mediated knock downs in zebra fish and Xenopus , where syntenin is required for polarized early embryonic cell movements 48 , 49 .…”
Section: Discussionsupporting
confidence: 88%
“…In addition, SDCBP has also been reported to be related with cell migration, invasiveness and pseudopodia formation, all of which were connected with tumor metastasis . Swadesh et al also examined the potential role of SDCBP in melanoma and concluded that dysregulated SDCBP may function as a negatively regulator of melanoma invasion and metastasis . To sum up, our study suggested that miR‐23a could repress the development and progression of melanoma through the down‐regulation of SDCBP.…”
Section: Discussionsupporting
confidence: 52%
“…Tumor-stroma interactions play a prominent role in the evolution of cancers. In contrast with the role of host-syntenin in melanoma progression 22 , we here provide evidence that leukemic blasts confronted with a syntenin-negative environment acquire a cell-autonomous advantage and aggressiveness.…”
Section: Discussioncontrasting
confidence: 84%
“…In comparison, the impact on tumor development resulting from syntenin suppression in the tumor microenvironment remains under-explored. Syntenin-deficiency of the host was shown to reduce melanoma metastasis, by dampening tumor-supporting inflammation 22 .…”
Section: Introductionmentioning
confidence: 99%